Catalytically Graphitized Nanostructured Carbon Xerogels as High Performance Anode Material for Lithium Ion Battery. (5th April 2018) - Gaikwad, Mayur; Kakunuri, Manohar; Sharma, Chandra Shekhar
Abstract : Resorcinol formaldehyde (RF) xerogel is an organic precursor to hard carbon which is catalytically graphitized at 1100 °C in nitrogen atmosphere with two different catalyst loading (2 and 5 wt.%). The effect of catalyst loading during graphitization and later its removal is studied in terms of physiochemical properties of RF xerogel derived hard carbon using XRD, Raman spectroscopy and FESEM. Electrochemical performance of the as-prepared catalytically graphitized RF xerogel derived nanostructured carbon has been studied using cyclic voltammogram and galvanostat/potentiostat experiments. For 5 wt.% catalyst loading, a reversible capacity of 192 mAh/g was maintained with nearly 99% coulombic efficiency.